2021
DOI: 10.21608/jsre.2021.54341.1236
|View full text |Cite
|
Sign up to set email alerts
|

Using gamification in EFL vocabulary learning and learners’ attitudes toward gamification use

Abstract: Although gamification is one of the latest education trends, it has not been investigated adequately in the Egyptian EFL context. Hence, this mixed-method study aimed to explore the effect of using gamification on Egyptian EFL learners' vocabulary knowledge and their attitudes toward gamification use. The study followed a pre-posttest quasi-experimental research design. A total of 68 English Majors in the Faculty of Education at New Valley University participated in this study. The instruments included a vocab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Despite the scores, some students become less confident because they have limited knowledge in using online tools as not all students are trained the same way. In a study by Waer (2021) who explores learners' attitudes toward Quizizz usage, she found out that the students who used Quizizz in learning vocabulary, were excited and enjoyed their learning session, despite the poor internet access. Internet access is vital to operate all the online tools and it is almost impossible to conduct the lesson without a proper internet connection.…”
Section: Challenges Of Using Online Tools In Language Classroommentioning
confidence: 99%
“…Despite the scores, some students become less confident because they have limited knowledge in using online tools as not all students are trained the same way. In a study by Waer (2021) who explores learners' attitudes toward Quizizz usage, she found out that the students who used Quizizz in learning vocabulary, were excited and enjoyed their learning session, despite the poor internet access. Internet access is vital to operate all the online tools and it is almost impossible to conduct the lesson without a proper internet connection.…”
Section: Challenges Of Using Online Tools In Language Classroommentioning
confidence: 99%